Combined chemical and biological control of Fusarium graminearum: co-application of antagonistic bacteria removed from winter wheat leaves - Schulz, Milena (2015)
In the future Sweden needs to comply with EU directives which require the stronger implementation of Integrated Pest Management (IPM) which includes the reduction of the amount of pesticide applied in order to control plant pathogens such as Fusarium graminearum in wheat. The idea in this study was to compensate the reduced chemical control from the fungicide by the co-application of antagonistic bacteria which were isolated from winter wheat leaves. The aim was to test if a combination of antagonistic bacteria and a experimental dose (0.5 mg/l) of the fungicide Proline® provides an inhibition of fungal growth of F. graminearum in vitro (Dual culture assay) comparable to single fungicide application. The results showed that antagonistic bacteria are not affected by any of the used concentrations of the fungicide and provided additional inhibition of fungal growth. A experimental dose of the fungicide only reduced fungal growth rate during five days of incubation but did not stop it (mycelial area became equal to control after seven days incubation). The application of antagonistic bacteria however stopped fungal growth after seven days. The treatment effects were significant. From this it can be concluded that the coapplication of fungicides and antagonistic bacteria might be promising to provide sufficient control of fungal growth of F. graminearum provided bacteria survive in the environment they are applied to in a high concentration. As the present study only assessed treatment effects in the lab on agar further field experiments are needed to test the findings of the present study under real life conditions. The bacteria used in the present study were removed from wheat leaves and therefore might be able to survive, inoculated as biocontrol agents, on wheat leaves and wheat heads.